Проблеми використання криміналістичного обліку способів учинення злочинів в Україні - Панько, Н.А. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Рассматриваются проблемные вопросы использования криминального учета

способов совершения преступлений в Украине. Анализируется потребность

изменения и совершенстования таких учетов, сформулированы положения,

которые имеют элементы новизны и заслуживают внимания как с

теоретической, так и практической точек зрения. This paper considers the problematic aspects as to the use of the criminalistic registration of the means of the crime commitment in Ukraine. The author analyzes the necessity of modification and improvement of the registration. On the basis of the previous research considering the issues of the use of the criminalistic registration of the means of the crime commitment, the materials of the investigative practice, the author formulates the provision that includes some new elements and is important from the both theoretical and practical points of view.